Prevalence of maternal dietary iodine insufficiency in the north east of England: implications for the fetus. Issue 5 (20th August 2004) - Kibirige, M S; Hutchison, S; Owen, C J; Delves, H T
Abstract : Background: Maternal subclinical hypothyroidism is a cause of poor neurodevelopment outcome in the offspring. Although iodine deficiency is the most common cause of hypothyroidism world wide, there are no screening programmes for it in the United Kingdom where the population is assumed to be iodine replete. Objective: To determine the prevalence of reduced iodine intake by measuring urinary iodide concentrations in pregnant and non-pregnant women from the north east of England. Methods: Urinary iodide excretion (UIE) rate was estimated using inductively coupled mass spectrometry in 227 women at 15 weeks gestation and in 227 non-pregnant age matched controls. A reduced intake of iodine is indicated by a concentration in urine of less than 50 μg/l or less than 0.05 μg iodine/mmol creatinine. Results: Eight (3.5%) pregnant women and 13 (5.7%) controls had a reduced iodine/creatinine ratio. These values were higher when UIE was expressed as iodine concentration: 16 (7%) and 20 (8.8%) respectively. Ninety (40%) of the pregnant women had a UIE of 0.05–0.10, which is consistent with borderline deficiency. Conclusion: In this study, 3.5% of pregnant women had evidence of iodine deficiency, and 40% may be borderline deficient. Larger scale studies are required to estimate the true prevalence of iodine deficiency in the United Kingdom.